2019
DOI: 10.1088/1475-7516/2019/06/006
|View full text |Cite
|
Sign up to set email alerts
|

Biased tracers of two fluids in the Lagrangian picture

Abstract: We explore Lagrangian perturbation theory (LPT) for biased tracers in the presence of two fluids, focusing on the case of cold dark matter (CDM) and baryons. The presence of two fluids induces corrections to the Lagrangian bias expansion and tracer advection, both of which we formulate as expansions in the three linear modes of the Lagrangian equations of motion. We compute the linear-order two-fluid corrections in the Zeldovich approximation, finding that modifications to the bias expansion and tracer advecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 70 publications
(133 reference statements)
4
33
0
Order By: Relevance
“…This question was indeed investigated by using simulations with adaptive softening (Khoraminezhad et al 2021) and by using an extension of the separate universe approach (Barreira et al 2020a), which does not suffer from the numerical inaccuracies described above. These authors showed that halo formation is actually sensitive to baryon-dark matter fluctuations, in agreement with analytic arguments (Chen et al 2019;Schmidt 2016). At a fixed matter overdensity, halos tend to form more efficiently in regions with smaller baryon-dark matter differences.…”
Section: Baryonssupporting
confidence: 72%
“…This question was indeed investigated by using simulations with adaptive softening (Khoraminezhad et al 2021) and by using an extension of the separate universe approach (Barreira et al 2020a), which does not suffer from the numerical inaccuracies described above. These authors showed that halo formation is actually sensitive to baryon-dark matter fluctuations, in agreement with analytic arguments (Chen et al 2019;Schmidt 2016). At a fixed matter overdensity, halos tend to form more efficiently in regions with smaller baryon-dark matter differences.…”
Section: Baryonssupporting
confidence: 72%
“…fields. Similar behavior is seen in the evaluation of unequal-time correlation functions [47] and the baryon-cold dark matter cross-correlation [48,49], though the physical mechanisms are of course different. At large scales, we similarly have…”
Section: Real Spacesupporting
confidence: 58%
“…2 Ergo, we must 1 The CMB lensing power spectra we have computed for this work are available at https://github.com/sjforeman/cmblensing_ baryons. 2 There is hope that perturbation theory could provide such an analytical theory on quasi-linear scales, even in the presence of baryonic effects [45,46], but the corresponding predictions will still involve free parameters whose values must either be calibrated using simulations or fit to observations. resort to simulations that implement large-scale gravitational clustering alongside hydrodynamics and subgrid models of baryon behavior such as gas cooling, star formation, and feedback.…”
Section: A Methodsmentioning
confidence: 99%